TEACHING FOREIGN LANGUAGE AS ENGLISH - Ruziqulova Jasmina Yuldosh qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: Teaching foreign languages, especially English, has become a critical skill in today's globalized world. English, as a widely spoken language, serves as a tool for communication across various sectors, including business, science, and diplomacy. The ability to teach English effectively not only provides learners with valuable career and academic opportunities but also fosters cultural exchange and global understanding. This article explores the significance of teaching English, outlines key strategies such as Communicative Language Teaching (CLT) and Task-Based Learning (TBL), and highlights the role of technology in modern language education. It also addresses the challenges faced by educators, including student motivation, cultural barriers, and resource limitations. Ultimately, effective English language teaching can bridge gaps between cultures and provide learners with the skills necessary to thrive in a connected world.